THE AID TO MILITARY FAMILIES IN THE NORTH CAUCASUS DURING THE GREAT PATRIOTIC WAR - Elena Panarina (Гуманитарные и юридические исследования, 2021)
This article discusses the main types of assistance provided to the families of soldiers by the Soviet State and public organizations in the North Caucasus during the Great patriotic war. It proves the importance of the assistance support to the families of the front soldiers and the morale of the latter in the battles against the German-fascist invaders. The article provides information on providing military families with money from various sources. It examines the housing problem during the war years and the measures taken by the local authorities in various regions of the Northern Caucasus to provide military families with apartments, assist in the construction of individual houses, implement renovation of premises and supply with fuel. The article emphasizes the dependence of tackling the problem on personal attitude on the part of managers of enterprises and institutions, as evidenced by examples. It identifies the main types of food aid to military families, an assessment of the participation of local authorities and enterprises as well as trade union organizations in securing towns and promoting the processing of land parcels, ensuring farmers with seeds and farming equipment. The article specifies the priority of military families supply with consumer goods, provides information on the allocation of centralized funds of clothes, shoes and other household items, their repair, participation of labor collectives and the population of the Northern Caucasus. It stresses the importance of the patriotic movement to assist military families and the successes achieved in this work that contributed to the strengthening of the unity of the front and the rear, and the victory in the Great patriotic war.